Immediate Effect of Combination Therapy (Ultrasound and Interferential Therapy) on Pain in Adhesive Capsulitis Patients (Asian Journal of Pharmaceutics (AJP), 2025)
Background: Another name for adhesive capsulitis is frozen shoulder, is a debilitating illness that is marked by pain and progressive restriction in shoulder mobility, often due to synovial inflammation and capsular adhesions. The condition is particularly prevalent among females aged 40–65 and individuals with concomitant conditions such as diabetes and thyroid dysfunction. Conservative management, including therapeutic exercises and electrotherapy, is the standard approach, although limited access to physiotherapy in underserved areas necessitates strategies that yield immediate relief. Objectives: This study aimed to evaluate the immediate effects of combination therapy using Interferential therapy (IFT) and therapeutic ultrasound (US) on pain reduction in individuals suffering from adhesive capsulitis, compared to US therapy alone. Methods: An observational research with a prospective design was carried out using 78 participants diagnosed with adhesive capsulitis, randomly allocated into two groups. Group A received combination therapy (IFT + US) with tailored physiotherapy, while Group B received only US with physiotherapy. Pain intensity was measured before and after a single treatment session using the numeric pain rating scale (NPRS). Statistical analysis was conducted using paired and independent t-tests, with significance set at P < 0.05. Results: Both groups showed statistically significant reductions in NPRS scores posttreatment. However, Group A demonstrated a greater mean reduction (1.62) compared to Group B (1.03), with P = 0.000, indicating superior efficacy of combination therapy in immediate pain relief. Conclusion: Combination therapy involving IFT and US significantly reduces pain in a single session in individuals suffering from adhesive capsulitis, outperforming US alone. This approach may be especially beneficial in resource-limited settings where regular therapy sessions are not feasible. The findings support integrating multimodal electrotherapy strategies for more effective short-term management of adhesive capsulitis.